Channel Switching Behavior From Traditional Grocery Stores to Branded Grocery Chains in Karachi - Jaliawala, Muhammad Mubin; Rahman , Mustaghis ur (JISR management and social sciences & economics, 2014)
The advent of branded grocery chains has compelled customers to switch from traditional grocery stores to branded grocery chains or monthly grocery purchase. This phenomenon has been recently observed in Pakistan. The aim of this study is to explore the customers' level of switching over from traditional grocery stores to branded grocery chains and also to find out the determinants of switching over from traditional grocery stores to branded grocery chains in Karachi. This study is quantitative in nature and encompasses the Positivist paradigm. The deductive approach is employed and survey method is opted for in this research. As per the requirement of the theme, closed-ended questionnaire is used as research instrument and SPSS statistical software is employed for data analysis. As sampling strategy, convenience sampling technique is opted. Total of 105 valid questionnaires were received; 35 from each store i.e., Naheed Super Market, Imtiaz Super Store and Chaseup Departmental Store. To ascertain level of switching over it can be seen from the results that 90% of the respondents have been buying since four months and above from branded grocery chains. The research study reveals that the three independent variables (Proximity, Environment and Engagement) are correlated with channel switching with proximity having a low correlation.